Topoisomerase I Associates Specifically with Simian Virus 40 Large-T-Antigen Double Hexamer–Origin Complexes - Gai, Dahai (American Society for Microbiology, 2000)
Topoisomerase I (topo I) is required for releasing torsional stress during simian virus 40 (SV40) DNA replication. Recently, it has been demonstrated that topo I participates in initiation of replication as well as in elongation. Although T antigen and topo I can bind to one another in vitro, there is no direct evidence that topo I is a component of the replication initiation complex. We demonstrate in this report that topo I associates with T-antigen double hexamers bound to SV40 origin DNA (T(DH)) but not to single hexamers. This association has the same nucleotide and DNA requirements as those for the formation of double hexamers on DNA. Interestingly, topo I prefers to bind to fully formed T(DH) complexes over other oligomerized forms of T antigen associated with the origin. High ratios of topo I to origin DNA destabilize T(DH). The partial unwinding of a small-circular-DNA substrate is dependent on the presence of both T antigen and topo I but is inhibited at high topo I concentrations. Competition experiments with a topo I-binding fragment of T antigen indicate that an interaction between T antigen and topo I occurs during the unwinding reaction. We propose that topo I is recruited to the initiation complex after the assembly of T(DH) and before unwinding to facilitate DNA replication.